The Invisible Curriculum’s Influence on Youth’s Self-Identity and Self-Esteem Development - Nyamai, Dinah K. (Frontiers in Education, 2022)
This article sought to determine the role played by the invisible curriculum on young people’s view of self-including their self-identity and self-esteem. This comes against a backdrop of accusations and counter accusations regarding, on whose doorstep should the blame on young people’s vulnerability to risk behavior should be placed on, yet limited research, especially in Kenya, has given due consideration to the invisible curriculum. The invisible curriculum accounts for more than 90% of all students’ learning experiences including their self-conception or self-identity formation and people tend to behave in ways coherent with the view they have about themselves (self-identity). To fill this gap, a sequential explanatory research design was employed to answer one main questions: what role does accidental lessons arising from learning institutions’ social atmosphere play in young peoples’ self-identity and self-esteem development? The target population was 1246 and Yamane’s sample size calculation formula was used to determine the sample size which was 486. Stratified random sampling was used in selecting the respondents. A self-report questionnaire with 60-closed ended questions and an interview guide with 14 open-ended questions were used in data collection. The results confirmed that accidental lessons arising from invisible curriculum elements shape young people’s self-concept or self-identity and self-esteem.